The Impact of Gender on the Security Awareness of Sharjah Police in Preventing Electronic Fraud: a field study in the Emirate of Sharjah - Al Kaabi, Ali; Alomosh , Ahmad (Al-Adab Journal, 2025)
This research aims to investigate the impact of gender on the perception of the impact of security awareness provided by Sharjah Police in preventing electronic fraud, through a comprehensive field study conducted in the Emirate of Sharjah. A diverse sample of the emirate’s residents was selected, including citizens and residents of different nationalities, to ensure the diversity and comprehensiveness of the results. A detailed questionnaire was distributed to 254 participants, carefully designed to investigate the participants’ understanding of the security awareness provided, and its impact on their preventive behaviors towards electronic fraud. The study used advanced statistical analysis methods to identify gender differences in response to security awareness, and to analyze the effectiveness of this awareness in reducing electronic fraud incidents among different segments of society. The results indicated significant differences between males and females in the level of security awareness, as women showed a higher response to security awareness compared to men. The study also highlighted the importance of allocating awareness programs that are consistent with gender differences to enhance the effectiveness of awareness efforts. These results are expected to contribute to improving security awareness strategies and developing customized programs that take gender differences into account, thus enhancing the efficiency of Sharjah Police’s efforts to protect society from the risks of electronic fraud.